2019
DOI: 10.1016/j.ajpath.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Liver Regeneration after Acetaminophen Hepatotoxicity

Abstract: Acetaminophen (N-acetyl-para-aminophenol; APAP) overdose is the most common cause of acute liver failure in the Western world, with limited treatment opportunities. For years, research on APAP overdose has been focused on investigating the mechanisms of hepatotoxicity, with limited success in advancing therapeutic strategies. Acute liver injury after any insult, including APAP overdose, is followed by compensatory liver regeneration, which promotes recovery and is a crucial determinant of the final outcome. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 64 publications
4
143
0
1
Order By: Relevance
“…The best-described models to study liver regeneration after acute damage are (1) liver resection (partial hepatectomy [3]) and (2) toxicological damage [6]. The essential difference is that the latter induces parenchymatic necrosis, and hepatocyte proliferation is integrated into a complex wound healing response with fibrosis and inflammation [6]. In contrast, 2/3 liver resection activates cell division in the absence of any cellular lesion [3].…”
Section: The Regulation Of the Cell Cycle Signaling And Metabolism mentioning
confidence: 99%
“…The best-described models to study liver regeneration after acute damage are (1) liver resection (partial hepatectomy [3]) and (2) toxicological damage [6]. The essential difference is that the latter induces parenchymatic necrosis, and hepatocyte proliferation is integrated into a complex wound healing response with fibrosis and inflammation [6]. In contrast, 2/3 liver resection activates cell division in the absence of any cellular lesion [3].…”
Section: The Regulation Of the Cell Cycle Signaling And Metabolism mentioning
confidence: 99%
“…2,27,28 They can proliferate induced by various stimulating factors to compensate liver volume and restore liver function. 3,29 With the in-depth study of the liver regeneration process, it is found that miRNAs are closely linked to liver regeneration. 30 In this study, we demonstrated that PMPs-derived miR-25-3p promoted proliferation of HHL-5 cells via targeting the BTG2 gene in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as hepatocyte growth factor (HGF) are known to be crucial in liver regeneration, a continuous interest amongst researchers in their therapeutic application. However, higher concentrations of HGF in plasma were found in nonsurvivors as opposed to survivors, suggesting that interventions via other factors such as c-Met or TGF-ÎČ may be more effective for treatment [12]. In survivors, liver function is normally regained within three months.…”
Section: Figure 3: Acetaminophen Poisoning Treatment Optionsmentioning
confidence: 99%